If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(9x + 3) + -2 = 16 + 2x Reorder the terms: 4(3 + 9x) + -2 = 16 + 2x (3 * 4 + 9x * 4) + -2 = 16 + 2x (12 + 36x) + -2 = 16 + 2x Reorder the terms: 12 + -2 + 36x = 16 + 2x Combine like terms: 12 + -2 = 10 10 + 36x = 16 + 2x Solving 10 + 36x = 16 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 10 + 36x + -2x = 16 + 2x + -2x Combine like terms: 36x + -2x = 34x 10 + 34x = 16 + 2x + -2x Combine like terms: 2x + -2x = 0 10 + 34x = 16 + 0 10 + 34x = 16 Add '-10' to each side of the equation. 10 + -10 + 34x = 16 + -10 Combine like terms: 10 + -10 = 0 0 + 34x = 16 + -10 34x = 16 + -10 Combine like terms: 16 + -10 = 6 34x = 6 Divide each side by '34'. x = 0.1764705882 Simplifying x = 0.1764705882
| 8x=12x(x-.5) | | 4(P-7)=28 | | 3(5x-3)+2=13x-3 | | 4(4x-8)=8(-4+2x) | | y=2(3)+1 | | 3v+3v=-12 | | 5.5x=-209 | | 14-r=5 | | 13(P-18)=208 | | 2y+2x=-6 | | 552a/24=5250 | | 3x-(x-4)=5x+16 | | 4n+-6n=-8 | | -2(7w-1)+2w=2+2(2w-9) | | -x+4(x-8)=5x+8(x-5) | | 49=9w | | X-4.8=8.5 | | -6x=2y+10 | | 14-r=-5 | | y=2(2)+1 | | 2x^2+9+7=3 | | -7x+8=52+19x | | y=2(1)+1 | | 6y+7=67 | | 6x-8x+5=-2(x+2)+7 | | r-14=-8 | | -4n+2n=-6 | | 2xh*(x+h)= | | 1-4n-1=-12 | | -5(-9x+1)+9=6+8x | | 4x-4=-3x-13 | | 7x-3=81 |